The Impact of Positive Discipline as a Classroom Management Approach on Students’ Well-being and Academic Achievement: A Case Study in an International School in Cairo - Mahmoud Elkadi, Enas Ahmed Fathi; Sharaf, Rasha Saad (European Scientific Journal, ESJ, 2023)
This research is designed to identify the scope of positive discipline implementation as a classroom management approach in Groupe Scholaire Oasis (an international School in Cairo City) through investigating PD’s impact on studentsâ€™ well-being, and academic achievement. Researchers used a quantitative method through questionnaires applied on samples of students from two different age groups. Data analysis indicated that Positive Discipline approach as a Classroom Management Approach has a significant impact on studentsâ€™ well-being and academic achievement after six years of implementation. This significant impact is on students of different grades (3- 5 age group and 6 â€“ 9 age group). On the other hand, PDâ€™s impact on studentsâ€™ well-being and academic achievement differ according to age. The results showed that 3- 5 grades group was superior to the 3 â€“ 6 grades group with regard to: PD Seven Abilities, Student: Well-Being, and Approach to Learning (ATL) Skills.